Genome diversity and highland-adaptative variation in Tibet barley landrace population of China - Dondup, Dawa; Yang, Yang; Xu, Dongdong; Namgyal, Lhundrup; Wang, Zihao; Shen, Xia; Dorji, Tsechoe; kyi, Nyima; Drolma, Lhakpa; Gao, Liyun; Ga, Zhuo; Sang, Zha; et al. (Frontiers in Plant Science, 2023)
Barley landraces accumulated variation in adapting to extreme highland environments during long-term domestication in Tibet, but little is known about their population structure and genomic selection traces. In this study, tGBS sequencing, molecular marker and phenotypic analyses were conducted on 1,308 highland and 58 inland barley landraces in China. The accessions were divided into six sub-populations and clearly distinguished most six-rowed, naked barley accessions (Qingke in Tibet) from inland barley. Genome-wide differentiation was observed in all five sub-populations of Qingke and inland barley accessions. High genetic differentiation in the pericentric regions of chromosomes 2H and 3H contributed to formation of five types of Qingke. Ten haplotypes of the pericentric regions of 2H, 3H, 6H and 7H were further identified as associated with ecological diversification of these sub-populations. There was genetic exchange between eastern and western Qingke but they shared the same progenitor. The identification of 20 inland barley types indicated multiple origins of Qingke in Tibet. The distribution of the five types of Qingke corresponded to specific environments. Two predominant highland-adaptative variations were identified for low temperature tolerance and grain color. Our results provide new insights into the origin, genome differentiation, population structure and highland adaptation in highland barley which will benefit both germplasm enhancement and breeding of naked barley.